TRADITIONAL WORSHIPPING AND CONSERVATION OF PLANTS - Iyengar, S.; Sapru, Tripta; Gupta, A. (International Journal of Research -GRANTHAALAYAH, 2015)
The incredibility of India resides in its oneness inspite of diversity in culture, religion. Ethnic groups, castes, languages etc.; 31 states 1618 languages. 6400 castes, 6 ethic groups 29 major festivals and one country. Isliyemeradeshmahanhai. The diversity in culture and religion is reflected in diverse traditions faiths and beliefs. These faiths and beliefs in context with human relationship with supreme power has led to the protection and conservation of numerous plants thereby helping in maintenance of biodiversity. In Hindu families after a child is born ‘JanamPatrika’ is prepared depending on date time and place of birth to know his/her future. It is believed that rashi, nakshatra and positions of the navgraha at the time of birth has a great bearing on the nature and the events happening in the life of the child. There are twelve Janam (birth) rashis and twenty two nakshatras and nine navgahas (planets). Each of these is associated with a specific plant. It is believed that worshipping, Plantation and protection of plants associated with one’s birth rashi, nakshatra keeps at bay some of the adversities in life and also gives solutions to their problems. It would be interesting to study why when and how a particular species has come to be associated with above birth signs.